Live imaging of GLUT2 glucose-dependent trafficking and its inhibition in polarized epithelial cysts. Issue 7 (July 2014) - Cohen, Merav; Kitsberg, Daniel; Tsytkin, Sabina; Shulman, Maria; Aroeti, Benjamin; Nahmias, Yaakov
Abstract : GLUT2 is a facilitative glucose transporter, expressed in polarized epithelial cells of the liver, intestine, kidney and pancreas, where it plays a critical role in glucose homeostasis. Together with SGLT1/2, it mediates glucose absorption in metabolic epithelial tissues, where it can be translocated apically upon high glucose exposure. To track the subcellular localization and dynamics of GLUT2, we created an mCherry–hGLUT2 fusion protein and expressed it in multicellular kidney cysts, a major site of glucose reabsorption. Live imaging of GLUT2 enabled us to avoid the artefactual localization of GLUT2 in fixed cells and to confirm the apical GLUT2 model. Live cell imaging showed a rapid 15 ± 3 min PKC-dependent basal-to-apical translocation of GLUT2 in response to glucose stimulation and a fourfold slower basolateral translocation under starvation. These results mark the physiological importance of responding quickly to rising glucose levels. Importantly, we show that phloretin, an apple polyphenol, inhibits GLUT2 translocation in both directions, suggesting that it exerts its effect by PKC inhibition. Subcellular localization studies demonstrated that GLUT2 is endocytosed through a caveolae-dependent mechanism, and that it is at least partly recovered in Rab11A-positive recycling endosome. Our work illuminates GLUT2 dynamics, providing a platform for drug development for diabetes and hyperglycaemia.